Ultrafine cement in pressure grouting - Henn, Raymond W. (ASCE Press, 2010)
Ultrafine Cement in Pressure Grouting presents the technical and practical information required by engineers to plan and implement grouting programs that are cost effective and technically sound. As a key component of modern grouting programs, ultrafine cement is an ideal solution for geotechnical engineers and construction contractors who are grappling with the challenges of managing costs while developing sites that may be less than ideal. Increasingly, the virtues of ultrafine cement lead engineers and contractors to use it rather than the less-expensive portland cements.
Keywords: Grout (Mortar); Grouting (Soil stabilization) -- Materials.; Sealing (Technology) -- Materials.; elektronické knihy; electronic books